(untitled) (Agro Productividad, 2026)
Objective: To evaluate the effect of Phi application on the control of a grass weed population composed predominantly of stargrass (Cynodon nlemfuensis and C. plectostachyus) and native grasses (Axonopus spp., Cynodon spp., and Paspalum spp.) in sugarcane cultivation. Design/methodology/approach: Three 2 × 2 m plots were established to evaluate foliar spraying with 0, 400, and 800 mM Phi. The trial was conducted in a one-year-old ratoon sugarcane field. Toxicity level, damaged leaf area, and percentage of weed population controlled were assessed through image analysis using ImageJ software. Additionally, antioxidant activity and total chlorophyll concentration in leaf tissue were measured. Data were processed using RStudio version 1.2.5033 (analysis of variance and Tukey’s test). Results: Phi exhibited moderate toxicity at 400 mM and high toxicity at 800 mM. The predominant undesired vegetation included stargrass species (Cynodon nlemfuensis and C. plectostachyus) and native grasses of the genera Axonopus, Cynodon, and Paspalum. Despite clear foliar damage at both Phi concentrations, most weeds recovered within two to three weeks after application, indicating an efficient physiological strategy to counteract Phi-induced stress. This represents a challenge for the use of Phi as an herbicidal agent. Damaged leaf area reached 20.38 % at 400 mM and nearly 51 % at 800 mM Phi. Antioxidant activity increased with higher Phi concentrations, whereas total chlorophyll content declined as Phi dosage increased. Limitations on study/implications: This study focused solely on the effects of phosphorous acid-derived Phi on grass weeds in one-year-old sugarcane. Further research is needed to assess its impact throughout the crop cycle and on a broader range of grass weed species. Findings/conclusions: Foliar applications of 400 and 800 mM Phi caused moderate and severe phytotoxic effects, respectively, but were not sufficient to effectively control Poaceae weed populations in sugarcane.